Development of Activated Carbon from Cotton Fibre Waste as Potential Mercury Adsorbent: Kinetic and Equilibrium Studies - Jatindra N. Bhakta; Piyali Bhakta Majumdar; Yukihiro Munekage (International Journal of Chemical Engineering)
The study attempted to develop the activated carbon of cotton fibre (ACCF) from cotton waste as a high Hg2+ adsorbent media and characterize physicochemical properties using scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS) and Hg2+ adsorption kinetic by batch adsorption study with the function of contact time, solution pH, dosages of ACCF, and Hg concentration. The SEM-EDS study revealed that ACCF is composed of carbon (95.1%) and phosphorus pentoxide (4.9%). Obtained results of adsorption kinetics showed that 15 min of contact time is required to achieve the equilibrium state and wide range of pH (4.08–7) is favourable for maximum Hg adsorption. The Hg2+ adsorption capacity showed a decreasing trend with increasing dose of ACCF, whereas a reverse response of adsorption capacity was pronounced with increasing Hg concentration. The data was well described by Freundlich isotherm model and determined the high Hg2+ adsorption capacity of ACCF (169.2 mg/g). To our knowledge, the application of ACCF in removing Hg2+ is the first study. High Hg2+ adsorption capacity, economic feasibility, availability of cotton fibre waste, and simple preparation method concluded that it could be used as a novel low-cost and environmentally sound adsorbent media for removing high rate of Hg2+ from aqueous phase.